Bioaccumulation and health risk assessment of trace metal contamination in the musculature of the trahira fish (Hoplias malabaricus) from two neotropical rivers in southeastern Brazil - Leite, Lucas Aparecido Rosa [UNESP]; Pedreira Filho, Walter dos Reis; de Azevedo, Rodney Kozlowiski; Abdallah, Vanessa Doro (Elsevier, 2023)
Background: Fish are an important source of nutrition for humans. Artisanal fishing plays a fundamental role in Brazil fish production. In Brazil, the unrestrained increase, diffusion, and little importance for environmental causes of other economic activities, such as the agricultural industry, has caused irreparable damage, leading to the contamination of water bodies. Among the countless pollutants that reach water bodies, trace metals are extremely problematic. Here, we evaluated the bioaccumulation and health risk of trace metal contamination in the musculature of the trahira fish (Hoplias malabaricus), collected from two rivers in southeastern Brazil. Methods: During the period from May 2017 to November 2019, 90 fish were collected, 45 from each river. River water samples were also taken during the same collection periods. From fish, muscle tissue samples were taken, and together with river water samples, analyzed for the recovery of trace metals (Al, Cr, Mn, Fe, Ni, Cu, As, Cd, and Pb) through the technique of Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Results: In general, fish as well as the waters of the Jacaré-Guaçú River had higher concentrations of metals. The elements Al, Cr and Cd stood out from the others analyzed metals for having a hazard index (HQ) above 1 (Al), for being up to 10 times above the concentrations allowed by Brazilian legislation (Cr) and for having a high bioconcentration factor (Cd), indicating a biomagnification process through the food chain. Conclusion: In general, trace metal concentrations in the waters and fish of the Jacaré‐Guaçú were higher than in the Jacaré-Pepira, which shows that the Jacaré‐Guaçú is the one that suffers more anthropogenic action between the two rivers. In addition, some elements such as Al, Cr and Cd, due to its high concentrations, should receive some attention as they can pose risks to the health of fish, which can jeopardize the survival of their populations, and especially to humans who use these animals as a food source.
Keywords: Bioaccumulation; Hazard quotient; Heavy metal pollution; River pollution; Trace metal contamination